Essential Biomolecules in Food Webs - Ruess, Liliane; Müller-Navarra, Dörthe C. (Frontiers in Ecology and Evolution, 2019)
We here review the ecological role of essential nutritional biomolecules (fatty acids (FA), amino acids (AA), sterols, vitamins) in aquatic and terrestrial food webs, encompassing the forces behind their environmental distribution. Across ecosystems, mutualistic relationships frequently ensure exchanges of vitamins between producer and demander, especially between B12 and other B vitamins as well as the AA methionine. In contrast, FA, sterols and most AA are transferred up the food chain via classical predator-prey interactions, and therefore have good biomarker potential for trophic interactions. As biomass-flow depends on the absolute amounts of potential limiting biomolecules, considering solely their relative proportion in resources may under- or overestimate the availability for consumers. Moreover, if not accounted for, “hidden” trophic channels such as gut symbionts as well as metabolic conversion of precursor molecules can hamper food web analyses. Fundamental differences exist between aquatic and terrestrial ecosystems: Vitamin B12 produced by ammonium oxidizing Archaea is essential to many aquatic algae, whereas terrestrial plants escaped this dependency by using B12 independent enzymes. Long-chain 3 polyunsaturated FA (LC-3 PUFA) in aquatic systems mainly originate from planktonic algae, while in terrestrial systems belowground invertebrates can well be a source, also supporting aboveground biota. Interlinks from terrestrial to aquatic ecosystems are biochemically of total different nature than vice versa. While biomass rich in proteins and LC-3 PUFA is transferred to land, e.g. by trophic relationships, the link from terrestrial to aquatic ecosystems provides recalcitrant plant carbon, mainly devoid of essential nutrients, fuelling detrital food chains. Recent global changes influence food webs via altered input and transfer of essential biomolecules, but separating the effects of nutrients, CO2, and warming is not trivial. Current evolutionary concepts (e.g. Black Queen, relaxed selection) considering the costs of metabolic production partly explain food web dynamics, especially for vitamins, whereas adaptations to potential oxidative stress seem to be more important for LC-PUFA. Overall, for both heterotrophs and auxotrophs, the provision with essential biomolecules is precious. As these valuable nutrients often are kept unaltered in consumer metabolism, even in their stable isotope composition, offers a great advantage for their use as trophic markers.